Pengaruh Etika Profesi Dan Keahlian Audit Pada Kinerja Auditor Dengan Skeptisisme Profesional Auditor Sebagai Variabel Mediasi - Ardaleni, Ni Kadek Yunita; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 25 No 2 (2018), 2018)
The purpose of this study to determine the influence of professional ethics and audit expertise on the performance of auditors with professional skepticism of auditors as a mediation variable at the Public Accounting firm in Bali Province. This research was conducted at Public Accountant Office of Bali Province with seven offices in 2017 with 74 auditor number as sample through saturated sample method. Data collection was done by distributing questionnaires with 48 respondents who returned and 26 not used because of no return and 48 questionnaires that met the criteria through path analysis technique (path analysis). Based on the results of the analysis, professional ethics variables have positive and significant influence on the performance of auditors at Public Accounting Firm in Bali. Audit expertise has a positive and significant impact on the performance of auditors at Public Accounting Firm in Bali. Professional skepticism has a positive and significant influence on the performance of auditors at Public Accounting Firm in Bali. Professional auditor skepticism mediates the positive effect of professional ethics on the performance of auditors at Public Accounting Firm in Bali. Professional auditor skepticism mediates the positive influence of audit expertise on auditor performance at Public Accounting Firm in Bali Keywords : professional ethics, audit expertise, professional skepticism of auditors, on auditor performance .